The Development of Clioquinol Labeled-Gold Nanoparticles for the Treatment of Alzheimer’s Disease - Jung, Selice; Lee, Jooyeong (Technium BioChemMed, 2024)
Clioquinol has emerged as a prominent metal-chelating agent for Alzheimer’s Disease. While clioquinol was once a popular antibiotic for skin infections, it has recently been investigated as a potential therapeutic for Alzheimer’s Disease. Its metal chelating property can restore metal homeostasis and prevent copper (Cu2+) and zinc (Zn2+) from interacting with amyloid-β (Aβ) peptides. Here, we propose labeling gold nanoparticles with clioquinol as a novel therapeutic approach for Alzheimer’s Disease to enable effective delivery of the agent across the blood-brain barrier. Based on previous studies on the individual efficacies of clioquinol and gold nanoparticles, we anticipate that this approach will prevent the formation of Aβ oligomers by disrupting metal-protein interactions. Our proposed clioquinol-labeled gold nanoparticles provide a novel curative approach for Alzheimer’s Disease and insights into subsequent therapeutic developments.